The Effectiveness of Narrative Exposure Therapy on Improving Posttraumatic Symptoms and Interpersonal Reactivity in Patients With Cancer - Sajjad Basharpoor; Sholeh Amani; Mohammad Narimani (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective As a universal problem, cancer is the third cause of deaths in Iran. Recent advances in the treatment of this disease have been led to the prolonged life of these patients and increased the importance of paying attention to their psychological adaptation to the disease. Since the disease is a threat to individual life, perceiving the diagnosis of this disease can cause post-traumatic symptoms and intensify the psychological reactivity of the individual. This study conducted in order to investigate the effectiveness of Narrative Exposure Therapy (NET) on reducing the post-traumatic symptoms and interpersonal reactivity in patients with cancer. Materials & Methods This research is a pilot experimental study with pretest-posttest design with a control group. The statistical population of this study included all female cancer patients with Post-Traumatic Stress Disorder (PTSD), admitted to the Blood and Oncology Department of Motahari Hospital of Foulad Shahr of Isfahan from July to September of 2016, and had completed complementary and maintenance chemotherapy and radiology treatments. To select the subjects, the list of all patients with cancer diagnosis was obtained and after referring them to the site of the section and explaining the goals of this research, the scale of PTSD and the interpersonal reactivity were conducted to the all 63 hospitalizations and after collecting data, 30 of these people who had a score higher than 65 in the scale of Mississippi PTSD, and had malignant diagnosis were selected. In the next stage, structured clinical interviews, on the basis of DSM-5 criteria for the diagnosis of PTSD symptoms, and after confirmation of diagnosis, subjects were assigned to experimental group (n=15) and control group (n=15). The experimental group received 6 sessions of 90 minutes of NET, but the control group received no treatment. Collected data were analyzed by MANCOVA and ANCOVA tests using SPSS 18 software.  Results According to the results, after controlling for the pre-test effects, there was a significant difference between the mean scores of the two groups in the total score of the PTSD scale and the components of malicious memories, interpersonal communication, emotion control, depression, and two interactive reactivity components, namely, empathy and personal discomfort exist (P<0.05) indicating that NET has been effective in reducing symptoms of traumatic stress disorder and empathy and improving personal empathy and discomfort in cancer patients. But according to the results in the fantasy subscales, having a broad vision and overall stress response score did not find a significant difference between the two groups. Conclusion The results of this study revealed that NET can be an appropriate therapeutic program for reducing post-traumatic symptoms in patients with cancer because this intervention is based on the expression and retrieval of the traumatic event's details in a safe environment of therapy, but this intervention has less effect on interpersonal reactivity. Based on these results, it can be recommended using this intervention as an effective method for improvement of psychological problems related to diagnosing cancer along with biological treatments in patients with cancer.